Examination of a Telephone-Based Exercise Intervention for the Prevention of Postpartum Depression: Design, Methodology, and Baseline Data from The Healthy Mom Study - Lewis, Beth A (2012)
Research indicates that exercise is an efficacious intervention for depression among adults; however, little is known regarding its efficacy for preventing postpartum depression. The Healthy Mom study was a randomized controlled trial examining the efficacy of an exercise intervention for the prevention of postpartum depression. Specifically, postpartum women with a history of depression or a maternal family history of depression (n=130) were randomly assigned to a telephone-based exercise intervention or a wellness/support contact control condition each lasting six months. The exercise intervention was designed to motivate postpartum women to exercise based on Social Cognitive Theory and the Transtheoretical Model. The primary dependent variable was depression based on the Structured Clinical Diagnostic Interview (SCID). Secondary dependent variables included scores on the Edinburgh Postnatal Depression Scale, the PHQ-9, and the Perceived Stress Scale. The purpose of this paper is to describe the study design, methodology, and baseline data for this trial. Upon completion of the trial, the results will yield important information about the efficacy of exercise in preventing postpartum depression.